Manipulation of tissue factor-mediated basal PAR-2 signalling on macrophages determines sensitivity for IFNγ responsiveness and significantly modifies the phenotype of murine DTH - Wilkinson, Hannah; Leonard, Hugh; Robson, Michael G.; Smith, Richard; Tam, ElLi; McVey, John H.; Kirckhofer, Daniel; Chen, Daxin; Dorling, Anthony (Frontiers in Immunology, 2022)
Background: Tissue factor (TF) generates proteases that can signal through PAR-1 and PAR-2. We have previously demonstrated PAR-1 signalling primes innate myeloid cells to be exquisitely sensitive to interferon-gamma (IFNγ). In this work we explored how TF mediated PAR-2 signalling modulated responsiveness to IFNγ and investigated the interplay between PAR-1 / -2 signalling on macrophages. Methodology: We characterised how TF through PAR-2 influenced IFNγ sensitivity in vitro using PCR and flow cytometry. and how it influenced oxazolone-induced delayed type hypersensitivity (DTH) responses in vivo. We investigated how basal signalling through PAR-2 influenced PAR-1 signalling using a combination of TF-inhibitors and PAR-1 &-2 agonists and antagonists. Finally, we investigated whether this system could be targeted therapeutically using 3-mercaptopropionyl-F-Cha-Cha-RKPNDK (3-MP), which has actions on both PAR-1 and -2. Results: TF delivered a basal signal through PAR-2 that upregulated SOCS3 expression and blunted M1 polarisation after IFNγ stimulation, opposing the priming achieved by signalling through PAR-1. PAR-1 and -2 agonists or antagonists could be used in combination to modify this basal signal in vitro and in vivo. 3-MP, by virtue of its PAR-2 agonist properties was superior to agents with only PAR-1 antagonist properties at reducing M1 polarisation induced by IFNγ and suppressing DTH. Tethering a myristoyl electrostatic switch almost completely abolished the DTH response. Conclusions: TF-mediated signalling through PARs-1 and -2 act in a homeostatic way to determine how myeloid cells respond to IFNγ. 3-MP, an agent that simultaneously inhibits PAR-1 whilst delivering a PAR-2 signal, can almost completely abolish immune responses dependent on M1 polarisation, particularly if potency is enhanced by targeting to cell membranes; this has potential therapeutic potential in multiple diseases.